Splanchnic Vein Thrombosis Associated with Myeloproliferative Neoplasms: A Study of the AGIMM & IWG-MRT Groups in 519 Subjects - Pieri, Lisa; Guglielmelli, Paola; Primignani, Massimo; Betti, Silvia; Randi, Maria Luigia; Rumi, Elisa; Pascutto, Cristiana; Cervantes, Francisco; Ellis, Martin; Chen, Frederick; Delaini, Federica; Harrison, Claire N; et al. (Blood, 2014)
Philadelphia-negative Myeloproliferative Neoplasms (MPN), including Polycythemia Vera (PV), Essential Thrombocythemia (ET), Myelofibrosis (Primary [PMF] and secondary to PV and ET [PPV-, PET-MF] and unclassified MPN (U-MPN), are associated with an increased risk of venous thrombosis in unusual sites, such as splanchnic vessels (SVT). SVT can lead to complications such as portal hypertension, esophageal and gastric varices, ascites,hepatic failure and biliopathy. According to a meta-analysis MPN is the underlying cause of portal vein thrombosis (PVT) in 31.5% and Budd Chiari syndrome (BCS) in 40.9% of cases (Smalberg, 2012); a more in-depth analysis of clinical characteristics and evolution of MPN-associated SVT has been hampered by heterogeneity of cohorts comprising small number of cases. We conducted a retrospective multicenter study in patients (pts) with SVT associated with WHO2008-diagnosed MPN, with the aim to describe patient characteristics, disease course and prognostic factors with potential implications for clinical practice. Data were collected from 16 international hematologic centers in the framework of the Italian AGIMM and the IWG-MRT groups. We collected 519 cases of pts with PVT, splenic or mesenteric vein thrombosis (75.1%) and BCS (24.9%) associated with MPN. We used as comparator a cohort of 1686 controls (Ctr) represented by MPN without (w/o) SVT: 741 ET (43.9%), 684 PV (39.7%), 261 PMF (15.5%). Frequency of MPN associated with SVT was 37.8% ET (n=196), 36.8% PV (n=191), 15.4% MF (n=80), 10% U-MPN (n=52). Median follow-up was 89.9 months (mo) (range 0.5-430). For SVT vs Ctr group females were 54.5% vs 44.4% in PV (P=0.001), 68.4 vs 63.5% (p=0.13) in ET, 63.7% vs 29.1% in PMF (p<0.0001); median age at MPN diagnosis (dg) was 43.5 yr (range 12-90) vs 60.6 yr (range 12-93) (p<0.0001). Age at SVT dg was 44 yr (range 15-85). In 240 cases (46.7%) MPN and SVT dg were coincident, in 121 (23.6%) SVT occurred before MPN dg (median 26 mo, range 4-307) and in 153 (29.8%) during MPN follow up (median 68 mo, range 4-362). JAK2V617F mutation was found in 94% PV vs 94% in Ctr, 84% vs 61% ET (p<0.0001), 88.1% vs 68% PMF (p=0.006) and in 93% U-MPN. Erythropoietin-independent colonies (EEC) were evaluated in 111 SVT pts and found in 80 (72%), accounting for 38/48 PV (79%), 31/44 ET (70.5%), 9/12 PMF (75%) and 2/7 U-MPN (28.6%). At dg, SVT PV pts had lower hemoglobin levels than Ctr: median was 17.4 g/dL vs 18.5 g/dL (p<0.0001) in male, 16.9 g/dL vs 17.7 g/dL (p=0.0006) in female. A co-existing thrombophilic status was found in 38.5% SVT vs 11.8% of Ctr (p<0.0001). Recurrent SVT occurred in 12.2% of pts with a rate of 1.6% person/year (CI 1.2-2.1); risk of venous thrombosis other than SVT was increased in SVT group vs Ctr (p=0.02), with no difference for arterial thrombosis. Hemorrhage was more frequent in SVT group (32%) vs Ctr (7.2%)(p<0.0001), mainly related to esophageal varices, which were present in 66.9% of SVT pts. There was no difference in evolution to MF and acute leukemia (AL) for PV and ET pts with and w/o SVT, while risk of AL was lower in MF with SVT (p<0.00001). Overall survival was shorter in ET pts with SVT vs Ctr (p<0.0001). In PMF survival was better in SVT group (p<0.00001) and was associated with a higher proportion of SVT pts in lowest risk categories: IPSS low 65%, intermediate-1 20%, intermediate-2 10% and high 5% compared with 15%, 34%, 25% and 26% in Ctr group. At last FU, 79/519 pts (15.2%) had died; causes of death were evolution to AL (15.4%), other cancers (13.8%), disease progression without AL (10.8%), SVT (10.8%), hepatic failure and venous thrombosis other than SVT (7.7% each), heart failure and arterial thrombosis (6.2% each), hemorrhage (5.5%), renal failure and infection (4.6% each). Therapy after SVT included anticoagulation in 77%, antiaggregant in 21.2% and combination in 1.8%; 70% received cytotoxic drugs; 12.4% were treated with transjugular porto-systemic shunt. Beta blocker therapy was used in 48.5% of pts and correlated with improved survival (p=0.041) MPN associated with SVT correlated with younger age and female sex and might antedate the clinical phenotype in a quarter of the patients. MPN-associated SVT equally affected PV and ET, was more likely to occur in the presence of JAK2V617F or underlying thrombophilia and predicted recurrent venous but not arterial thrombosis. The apparent association of SVT with better or worse prognosis in PMF and ET, respectively, requires further investigation. No relevant conflicts of interest to declare.